A Sustainable Approach of Toaster by Using Simplified Life Cycle Assessment: A Case Study - Ruqayah Ali Grmasha, Osamah J. Al-sareji (International Journal of Advanced Science and Technology, 2020)
Toaster is considered the main appliances in every household worldwide. Thus, it is necessary toanalysis its life cycle and figures out which phase affects the environment and how its impacts couldbe alleviated. Simplified Life Cycle Assessment (SLCA) was conducted for the entire life cycle ofToaster considering raw materials phase, manufacturing phase, usage phase, End of life (EOL) andtransportation. According to SLCA results, the Polypropylene scored the highest SLCA points(approximate 0.2117) among the materials used in the Toaster. This can be expected as it contributesto the major weight of Toaster. Copper scored the second-highest SLCA points (0.1318) because of itsenvironmental impacts resulted from raw material extraction processes such as mining. This paperalso pointed out that the hot spot analysis during the manufacturing phase has resulted from plasticinjection moulding. In the life-cycle of Toaster, the obtained results of SCLA indicated that the usagephase had the highest SLCA points among all phases. This can result from the high consumption ofelectricity. After performing the sensitivity analysis, it is evidenced that replacing the conventionalfossil fuel to renewable wind power would have a less environmental impact during the life-cycle ofthe Toaster.